Ferocious things : Jean Rhys and the politics of women's melancholia - Maslen, Cathleen (Cambridge Scholars, 2009)
It's fatal making a fuss ...-Jean Rhys, Quartet. Cathleen Maslen's Ferocious Things: Jean Rhys and the Politics of Women's Melancholia closely engages with the most obvious theme of Rhys's writing: the speaking and inscription of feminine anguish. Maslen resists easy generalisations with respect to Rhys's portrayal of women's psychic pain, attending carefully to the nuances of sexual, cultural and ethnic displacement which inform the suffering of Rhys's protagonists. Acknowledging the m ...